2004
DOI: 10.1111/j.1365-2036.2004.1873.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with established inflammatory bowel disease: a UK general practice survey

Abstract: SUMMARYBackground: The current understanding of quality of life impairment in inflammatory bowel disease has largely been derived from selected populations and may not reflect the experience of patients in the community, where fewer than half are likely to be under specialist care. Aim: To describe the health-related quality of life in a community-based sample of patients with established inflammatory bowel disease and explore its association with the type and extent of disease, gender, age, material deprivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 16 publications
(28 reference statements)
3
45
1
2
Order By: Relevance
“…Thus, if sequential scores deteriorate with time, this is a reliable indicator of disease activity producing gastrointestinal, systemic and psychological symptoms. This has been demonstrated both in a primary-care setting as well as in hospital practice (Guyatt et al, 1989;Yoshida, 1999;Cheung et al, 2000;Rubin et al, 2004). In other words, in the setting of benign inflammatory disease, this questionnaire is highly reliable, and while we have not tested the reproducibility of scores in patients with stable symptoms in this study, there is little reason to think that this group of patients should score change in symptoms differently to those with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, if sequential scores deteriorate with time, this is a reliable indicator of disease activity producing gastrointestinal, systemic and psychological symptoms. This has been demonstrated both in a primary-care setting as well as in hospital practice (Guyatt et al, 1989;Yoshida, 1999;Cheung et al, 2000;Rubin et al, 2004). In other words, in the setting of benign inflammatory disease, this questionnaire is highly reliable, and while we have not tested the reproducibility of scores in patients with stable symptoms in this study, there is little reason to think that this group of patients should score change in symptoms differently to those with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 86%
“…Research involving community-based IBD samples has produced mixed conclusions regarding the negative impact of the disease on psychological functioning [22][23][24] . A study that used health records to identify 400 cases, concluded that those with IBD had only minor impairment overall in quality of life domains including general physical symptoms, social functioning, and emotional wellbeing 22 .…”
Section: Introductionmentioning
confidence: 99%
“…A study that used health records to identify 400 cases, concluded that those with IBD had only minor impairment overall in quality of life domains including general physical symptoms, social functioning, and emotional wellbeing 22 . This study found more pronounced difficulties for women and those with…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is a form of inflammatory bowel disease (IBD) which affects mainly the colon, thus causing abdominal pain, bloody diarrhea and weight loss. Both diseases may cause significant morbidity and diminished life quality [1,2,3,4,5,6]. Treatment options include a variety of anti-inflammatory and immunosuppressant agents.…”
Section: Introductionmentioning
confidence: 99%